The Role of Environmental Law Enforcement in Improving Company Compliance with Hazardous Waste Management Regulations - Judijanto, Loso; Saputra, Citra Dewi (West Science Law and Human Rights, 2025)
The mismanagement of hazardous waste remains a critical environmental issue in Indonesia, posing significant risks to public health and ecological sustainability. This study examines the role of environmental law enforcement in improving corporate compliance with hazardous waste management regulations through a juridical analysis. Findings reveal that while Indonesia has comprehensive regulatory frameworks, enforcement effectiveness is hindered by limited resources, overlapping authorities, and insufficient penalties. Larger corporations demonstrate higher compliance rates, driven by reputational concerns, while small and medium enterprises face challenges due to resource limitations and lack of awareness. The study underscores the need for stronger enforcement mechanisms, enhanced community participation, and integration of technology to improve regulatory compliance. Recommendations include streamlining legal frameworks, increasing enforcement capacity, and fostering public-private partnerships to achieve sustainable hazardous waste management in Indonesia.